REALITIES AND DISCOURSES ON SOUTH AFRICAN XENOPHOBIA (The Strategic Review for Southern Africa, 2020)
The responses to the January 2015 looting of foreign-owned shops inSoweto and in April in Durban's central business district and elsewhere reveal more about the South African national consciousness than the events themselves. The ritual condemnations; the initial denial of xenophobia in preference to labelling it criminality; blaming victims and convoluted excuses of perpetrators are almost worse than the official silence and long-standing passivity about well-known xenophobic attitudes. When the President insists that "South Africans in general are not xenophobic", he ignores all surveys (Afrobarometer) showing a vast majority distrust (black) foreigners, wish to restrict their residence rights and prohibit the eventual acquisition of citizenship.On these scores South African attitudes are not unique. Antiimmigrant hostility inflicts most European societies. Perhaps suspicion of strangers is even universal: preferential kin selection as an evolutionaryadvantage, as sociobiologists assert. What is uniquely South African is the ferocious mob violence against fellow Africans. Why? The structural violence of apartheid laws has continued in the post-apartheid era for many reasons: the breakdown of family cohesion in poor areas which no longer shames brutalised youngsters; loss of moral legitimacy by government institutions, particularly a dysfunctional justice system; violence was glorified in the 'armed struggle', but, above all, marginalised slum dwellers learned that they only receive attention when they act destructively. Despite a rule bound constitution for conflict resolution, in a representative survey (Afrobarometer) 43 per cent in the Western Cape agreed with the suggestion that "it is sometimes necessary to use violence in support for a just cause".
Keywords: Looting; Soweto; Durban; South Africa; xenophobia; Afrobarometer; Anti-immigrant; violence; Africans; sociobiologists; structural violence; apartheid; post-apartheid; cohesion; government institutions; legitimacy; armed struggle; marginalised; constitution; conflict resolution; Western Cape; US-Africa Leaders Summit; Nelson Mandela; rainbow nation; civil society organisations; amakwerekwere; ANC; SACP